Is there a zero lower bound? The effects of negative policy rates on banks and firms - Carlo Altavilla; Lorenzo Burlon; Mariassunta Giannetti; Sarah Holton (European Central Bank (ECB), 2019)
Exploiting confidential data from the euro area, we show that sound banks can pass negative rates on to their corporate depositors without experiencing a contraction in funding. These pass-through effects become stronger as policy rates move deeper into negative territory. Banks offering negative rates provide more credit than other banks suggesting that the transmission mechanism of monetary policy is not hampered. The negative interest rate policy (NIRP) provides further stimulus to the economy through firms' asset rebalancing. Firms with high current assets linked to banks offering negative rates appear to increase their investment in tangible and intangible assets and to decrease their cash holdings to avoid the costs associated with negative rates. Overall, our results challenge the commonly held view that conventional monetary policy becomes ineffective when policy rates reach the zero lower bound.
Keywords: E52; E43; G21; D22; D25; 330